2019
DOI: 10.3390/biom9120858
|View full text |Cite
|
Sign up to set email alerts
|

Herbal Extracts Incorporated into Shortbread Cookies: Impact on Color and Fat Quality of the Cookies

Abstract: This study aimed at determining the effect of aqueous ethanolic extracts from lemon balm, hyssop and nettle, and butylated hydroxyanisole (BHA) on properties of shortbread cookies. This was achieved by instrumental measurements of color and sensory properties of the cookies directly after baking and by determination of peroxide (PV) and p-anisidine (p-AnV) values, and specific extinction coefficients (K 232 and K 268 values) for fat extracted from the cookies stored for 3 months at room temperature. Increase o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…UV absorption changes at 232 and 268 nm, measured as K232 and K268, provide insights on the degree of oxidative damage of lipids [ 60 ]. It was found that K232 is strongly correlated with the level of conjugated dienes (CDs) produced as a consequence of the primary oxidation process of polyunsaturated fatty acids, while K268 is more closely linked to the presence of conjugated trienes (CTs) and carbonyl compounds formed in response to secondary lipid oxidation processes [ 26 ]. CDs and CTs accumulate and are stable in the oil samples exposed to high temperatures and their assessment has been shown to be adequate to estimate the lipid oxidation status [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…UV absorption changes at 232 and 268 nm, measured as K232 and K268, provide insights on the degree of oxidative damage of lipids [ 60 ]. It was found that K232 is strongly correlated with the level of conjugated dienes (CDs) produced as a consequence of the primary oxidation process of polyunsaturated fatty acids, while K268 is more closely linked to the presence of conjugated trienes (CTs) and carbonyl compounds formed in response to secondary lipid oxidation processes [ 26 ]. CDs and CTs accumulate and are stable in the oil samples exposed to high temperatures and their assessment has been shown to be adequate to estimate the lipid oxidation status [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, data from Table 5 reveal the increases registered in K268, associated with CT accumulation in SFO samples, with the increasing exposure time at a high temperature up to 8 h. These changes are closely related to the generation of secondary lipid oxidation products, usually found in vegetable oils undergoing advanced oxidative processes [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Caleja et al (133) found that the addition of synthetic BHA additives or natural extracts gave similar AA to biscuits. In addition, Kozlowska et al (136) prepared cookies by adding extracts of hyssop, nettle, or lemon balm and substituting some of the palm fat with walnut oil (cold-pressed). Although including hyssop or lemon balm extracts in the formulation of cookies may increase their quality and appeal to consumers, synthetic antioxidant BHA (0.02%) was still a more efficient inhibitor of lipid oxidation than herbal extracts (136).…”
Section: Pastriesmentioning
confidence: 99%
“…This type of food is aimed at people with elevated blood glucose levels and used in the manufacture of food for obese patients. Technologists design such food products [17], and consumers increasingly seek such food [18]. In recent years, there has been a considerable and observable emphasis, or at least fashion, as to the maintenance of full health and vitality even in old age.…”
Section: Introductionmentioning
confidence: 99%